Influence of the Bias Potential and Working Gas Pressure on the Properties of the TiSiN/NbN Ion Plasma Multilayer Coating - Horokh, D. V.; Maksakova, O. V.; Klymenko, S. A.; Lytovchenko, S. V.; Beresnev, V. M.; Glukhov, O. V. (My University, 2022)
The phase composition, element distribution, and mechanical properties of the TiSiN/NbN(TiN) multilayer coatings obtained by vacuum arc deposition are anlyzed. The effect of the bias potential on the mechanical and tribological characteristics of the coatings is studied, and the adhesion strengths of the coatings to the substrate are measured. The results of X-ray diffraction stud ies of the coatings show that a two-fold increase in the bias potential leads to increases in all phase and structural parameters—in particular, lattice parameters, crystallite sizes, and microdeformation levels of the components of the coatings. The intensities of δ diffraction peaks of TiN and NbN indicate the presence of a strong (200) texture. Tribotechnical studies of the coatings have shown that they are erased during scratching, but their detachment from the substrate has not been recorded. This means that the coatings are worn by the cohesive mechanism associated with plastic deformation and the for mation of fatigue cracks in the coating volume. Different modes of coating formation correspond to different values of acoustic emission that occurs, depending on the conditions, in the loading zone.
Keywords: vacuum–arc sputtering; multilayer coatings; bias potential; hardness; adhesive strength